Spin the light off: rapid internal conversion into a dark doublet state quenches the fluorescence of an RNA spin label. Issue 38 (21st September 2017) - Gustmann, Henrik; Lefrancois, Daniel; Reuss, Andreas J.; Gophane, Dnyaneshwar B.; Braun, Markus; Dreuw, Andreas; Sigurdsson, Snorri Th.; Wachtveitl, Josef
Abstract : The fluorescence of the RNA spin labelÇm is quenched via rapid internal conversion into a dark doublet state, which is localized on the nitroxide group of the FNRO˙ compound. Abstract : The spin labelÇm and the fluorophoreÇm f are close isosteric relatives: the secondary amineÇm f can be easily oxidized to a nitroxide group to formÇm . Thus, both compounds can serve as EPR and fluorescence labels, respectively, and their high structural similarity allows direct comparison of EPR and fluorescence data, e.g. in the context of investigations of RNA conformation and dynamics. Detailed UV/vis-spectroscopic studies demonstrate that the fluorescence lifetime and the quantum yield ofÇm f are directly affected by intermolecular interactions, which makes it a sensitive probe of its microenvironment. On the other hand, Çm undergoes effective fluorescence quenching in the ps-time domain. The established quenching mechanisms that are usually operational for fluorophore-nitroxide compounds, do not explain the spectroscopic data forÇm . Quantum chemical calculations revealed that the lowest excited doublet state D1, which has no equivalent inÇm f, is a key state of the ultrafast quenching mechanism. This dark state is localized on the nitroxide group and is populated via rapid internal conversion.